Monetary Policy in an Endogenous Growth Model with R&D and Human Capital Accumulation - Sequeira, Tiago Miguel Guterres Neves (2020)
Despite some recent evidence according to which different inflation rates have effects on long run growth, endogenous growth theory had advanced little on explaining the mechanics of monetary influence on economic growth. We follow the increasing interest in the issue offering a new explanation for the influence of monetary policy on growth in both long and short run: the cash requirements for households expenditures in education. Quantitatively, the model replicates both the small influence of monetary policy on growth while also highlighting the effects it can have on welfare and allocations of resources throughout different sectors in the economy.